The Australian Radio Quiet Zone - Western Australia: Objectives, implementation and early measurements - Wilson, C.; Chow, K.; Harvey-Smith, L.; Indermuehle, B.; Sokolowski, M.; Wayth, Randall (2016)
The Australian Radio Quiet Zone - Western Australia (ARQZWA) has been established to protect new generation radio astronomy instruments, including the Australian component of the Square Kilometre Array (SKA). Using characteristics of typical transmitters and applying propagation prediction methods, various zones were established with appropriate protection measures. Legislation and regulatory policy has been implemented at Commonwealth and State level to protect the site from terrestrial radio transmissions and incidental emissions. Radio frequency interference detected by telescopes on the site has originated from distant sources, typically via anomalous propagation. The quietness of the site is already demonstrated in new astronomical discoveries.